INOCULAÇÃO COM AZOSPIRILLUM BRASILENSE E BRADYRHIZOBIUM JAPONICUM NA CULTURA DO MILHO E DA SOJA - NOGUEIRA, Laizi Azevedo; ANDRADE, Dener Coelho; MEDEIROS, Carolina Drews; OLIVEIRA, Luiz Anderson Abdalla; PAULINO, Luiz Loesia Gomes; SILVA, Matheus Gustavo (ANAIS DO ENIC, 2020)
-